OPTIMISASI DENGAN METODE PENCARIAN LANGSUNG BERARAH - , KIRTYANA NINDITA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Optimization is not only used on differentiable functions. In some conditions, optimization must be used on non differentiable functions, although they donât have derivative information that is needed for optimality condition of the function. Because of that, we need some derivative-free method for optimization. Directional direct-search method is one of derivative-free optimization that is easy enough to understand. This method is done by trying to evaluate the objective function at finite number of points in each iteration by using positive basis as a set of directions. In this final project, we discuss about directional direct-search method, especially the global convergence of this method. At first, we discuss about global convergence for continuously differentiable function with infinite and finite positive bases. Then we continue to discuss about global convergence that is not guaranteed for non differentiable function. Next, we discuss about directional direct-search method equipped by simple decrease condition and sequence of iterates that forms integer lattices. In the last section we discuss about directional direct-search method equipped by sufficient decrease condition.